Pelabelan Produk Pangan Yang Mengandung Bahan Rekayasa Genetik - Neng Melly Senisa; Rory Jeff Akyuwen; Agustina Balik (PATTIMURA Law Study Review, 2023)
Indonesian legislation relating to genetically engineered food is Law Number 7 of 1996 concerning Food and Government Regulation Number 69 of 1999 concerning Food Labels and Advertisements. Article 35 states that the label for genetically engineered food must include the words Genetically Engineered Food in the name of the type. Information as a genetic engineering product on the label has been regulated by BPOM Number 6 of 2018 concerning Supervision of Genetically Engineered Food Products, in Article 8 and Article 9 concerning Food Labels for Genetically Engineered Products. Genetically engineered food products have long entered the Indonesian market. However, in reality, in Indonesia until now there are no food products that carry labels as required by these regulations. The method used in this research is normative juridical using a statutory approach and a conceptual approach. The sources of legal materials used in this research are primary legal materials, secondary legal materials and tertiary legal materials. Based on the research results, it was found that business actors who produce products containing genetically engineered ingredients have a responsibility to ensure the safety of the products produced and fulfill obligations regarding food product labeling by including a label that says Genetically Engineered Products (PRG). The legal consequences for producers or people who produce or import food that does not carry the genetic engineering label are that they may be subject to legal sanctions. Legal sanctions include fines, temporary closure or revocation of business permits, and/or criminal charges. So every food product that enters Indonesian territory should comply with the regulations regulated in Indonesia.